Integrin αIIbβ3 outside-in signaling activates human platelets through serine 24 phosphorylation of Disabled-2 - Hui-Ju Tsai; Ju-Chien Cheng; Man-Leng Kao; Hung-Pin Chiu; Yi-Hsuan Chiang; Ding-Ping Chen; Kun-Ming Rau; Hsiang-Ruei Liao; Ching-Ping Tseng (Cell & Bioscience, 2021)
Abstract Background Bidirectional integrin αIIbβ3 signaling is essential for platelet activation. The platelet adaptor protein Disabled-2 (Dab2) is a key regulator of integrin signaling and is phosphorylated at serine 24 in eukaryotic cells. However, the mechanistic insight and function of Dab2-serine 24 phosphorylation (Dab2-pSer24) in platelet biology are barely understood. This study aimed to define whether and how Dab2 is phosphorylated at Ser24 during platelet activation and to investigate the effect of Dab2-pSer24 on platelet function. Results An antibody with confirmed specificity for Dab2-pSer24 was generated. By using this antibody as a tool, we showed that protein kinase C (PKC)-mediated Dab2-pSer24 was a conservative signaling event when human platelets were activated by the platelet agonists such as thrombin, collagen, ADP, 12-O-tetradecanoylphorbol-13-acetate, and the thromboxane A2 activator U46619. The agonists-stimulated Dab2-pSer24 was attenuated by pretreatment of platelets with the RGDS peptide which inhibits integrin outside-in signaling by competitive binding of integrin αIIb with fibrinogen. Direct activation of platelet integrin outside-in signaling by combined treatment of platelets with manganese dichloride and fibrinogen or by spreading of platelets on fibrinogen also resulted in Dab2-pSer24. These findings implicate that Dab2-pSer24 was associated with the outside-in signaling of integrin. Further analysis revealed that Dab2-pSer24 was downstream of Src-PKC-axis and phospholipase D1 underlying the integrin αIIbβ3 outside-in signaling. A membrane penetrating peptide R11-Ser24 which contained 11 repeats of arginine linked to the Dab2-Ser24 phosphorylation site and its flanking sequences (RRRRRRRRRRR19APKAPSKKEKK29) and the R11-S24A peptide with Ser24Ala mutation were designed to elucidate the functions of Dab2-pSer24. R11-Ser24 but not R11-S24A inhibited agonists-stimulated Dab2-pSer24 and consequently suppressed platelet spreading on fibrinogen, with no effect on platelet aggregation and fibrinogen binding. Notably, Ser24 and the previously reported Ser723 phosphorylation (Dab2-pSer723) occurred exclusively in a single Dab2 molecule and resulted in distinctive subcellular distribution and function of Dab2. Dab2-pSer723 was mainly distributed in the cytosol of activated platelets and associated with integrin inside-out signaling, while Dab2-pSer24 was mainly distributed in the membrane fraction of activated platelets and associated with integrin outside-in signaling. Conclusions These findings demonstrate for the first time that Dab2-pSer24 is conservative in integrin αIIbβ3 outside-in signaling during platelet activation and plays a novel role in the control of cytoskeleton reorganization and platelet spreading on fibrinogen.